Promoting Creativity in Computing Education - Sutinen, E. (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
Computing is a family of sciences related to data, information and knowledge processing (Denning et al., 1989). It is an umbrella term that covers computer science, computer engineering, information and communication technology, software engineering, and information systems. Computing education refers to any form of teaching, training, or learning activities that aim at understanding a topic within computing. Computing education research (CER) is an academic research field that develops, designs, conceptualizes, and evaluates methods, practices or phenomena in computing education. Based on its agenda, CER lies in the intersection of computing and any of its application areas, and education and any of its sub-specializations.